Evaluation of Caribbean Integrated Science Projects - Reay, Judith F.
This paper presents a case study on curriculum evaluation for science education in the Caribbean area. It describes five projects for an integrated curriculum for science as part of the lower secondary school curriculum. It also examines regional cooperation related to curriculum development and educational innovation in the area
Keywords: Curriculum evaluation